TERRESTRIAL RADIANT ENERGY EXCHANGES ACROSS TROPOPAUSE OVER PUNE - DESIKAN, V.; JAYARAMAN , K.; BHAGWAT, S.P. (MAUSAM, 1994)
Fort nightly auuusphe ric sound ings """ilh radiomete r are bei ng made al Pu ne after th e sunset The dam obtained o ver an (" iih t yea r pe riod. 1978-1985 an d on occasions ....'hen th ese so unl.Hnis reac hed stratosp here h aw bee n studied in o rde r 10 obta in a pictu re of th e terr estri al radiant ene rgy excha nges (infrared rad iative !lux exchanges) Berms the tropopause. It is Iound th ai th e tropopause .:ene raJly loses energy almust th rough out the year exceru du ring the monso on period . Th e net lo ss in rad iant euC' rgy by the tropo pause is 1.4Wm - ~. Th e losses in th e pre-monsoo n and th e post -monsoon pe riod s are respectivel y 3.4 Wm - =an d 41 Wrn - ~ . whereas the gai n du ring th e monsoon .'Il!'IIS(ln is 5.2 Wm - : . Winh' r losses amo um rc 6.ft Wm - ~ , These valu es. however, vary wide ly in individual ca ses depc nding upon th e sky cover. ROl l the d epth nf water vapo ur ..:o lumo .